2002
DOI: 10.1002/jrs.827
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of dimethyl sulphoxide and deuterated dimethyl sulphoxide at 298 and 77 K

Abstract: Raman spectroscopy was used to determine the molecular behaviour of DMSO and DMSO-d 6 , and to compare it with that of DMSO in DMSO-intercalated kaolinites. For DMSO at 298 K two bands are observed at 2994 and 2913 cm −1 and are assigned to the antisymmetric and symmetric CH stretching modes. At 77 K the degeneracy of these bands is lost. Bands are now observed as antisymmetric bands at 3001, 2995 and 2988 cm −1 and symmetric bands at 2923, 2909 and 2885 cm −1 , respectively. For the DMSO-intercalated low-defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 14 publications
7
62
1
Order By: Relevance
“…Raman peaks at 1046, 1424, 2919 and 3005 cm −1 , together with the double peak at 671 and 699 cm −1 , are clearly identifiable. All the detected peaks match well the values reported in the literature [7].…”
Section: Resultssupporting
confidence: 89%
“…Raman peaks at 1046, 1424, 2919 and 3005 cm −1 , together with the double peak at 671 and 699 cm −1 , are clearly identifiable. All the detected peaks match well the values reported in the literature [7].…”
Section: Resultssupporting
confidence: 89%
“…The spectral subtraction reveals the presence of the DMSO peaks located at 699.7, 958.9 and 1046.7cm −1 , in addition to those appearing at 671.2, 1424.4, 2919.9 and 3001.2cm −1 , already visible in the original (unsubtracted) spectrum. These peaks are in good agreement with the work by Martens et al [33], assumed as a reference and indicated between parentheses in Fig. 6 for comparison.…”
Section: Double-clad Fiber Probesupporting
confidence: 92%
“…The shift of the DMSO C-S antisymmetric stretch with InCl3 addition from 698 cm -1 to 720 cm -1 (and DMSO S=O stretch from 1042 cm -1 to 1005 cm -1 , Figure S1) is unaffected by the addition of thiourea. 30 Furthermore, the C=S stretch of thiourea (at 746 cm -1 ) is unaffected by InCl3 addition. In contrast, the C=S stretching mode of thiourea is significantly lowered by the addition of CuCl to the ink.…”
Section: Broader Contextmentioning
confidence: 99%